Gymnastics of molecular chaperones - Mayer, Matthias P. (Molecular cell, 2010)
Molecular chaperones assist folding processes and conformational changes in many proteins. In order to do so, they progress through complex conformational cycles themselves. In this review, I discuss the diverse conformational dynamics of the ATP-dependent chaperones of the Hsp60, Hsp70, Hsp90, and Hsp100 families.